The double porch, the most significant typological invariantin the nineteenth-century domestic architecture of Sinaloa - Valenzuela Escalante, Sergio Antonio (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
This paper deals with the genesis and develop- ment of the typological invariant that identifies the housing of the state of Sinaloa in the history of the domestic architecture in the sinaloan terri-ory.  It is a subject that allows access to knowledge of the evolution of housing, based on documentary evidence and material evidence. This is done by referring to the long-term historical time at the same level as the pre-Hispanic, viceregal and nineteenth-century structures. Here, from the typologies, the development of the space dedicated to housing throughout history is characterized. The analysis in this work is adjusted to the guidelines set by the history sciences, and for consistency to the conservation of cultural heritage. Where cultural expressions are approa- ched from the everyday in a sociocultural context conditioned by the isolation that determined the distance and farness, in a society that lived in isolation and that nevertheless, at the end of the 19th century it produced a typological constant identified as the sinaloan double porch.